2012
DOI: 10.1103/physrevlett.109.196602
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Planar Nernst Effect in Permalloy and Nickel Thin Films with In-Plane Thermal Gradients

Abstract: We present experimental evidence of a transverse thermopower, or planar Nernst effect, in ferromagnetic metal thin films driven by thermal gradients applied in the plane of the films. Samples of 20 nm thick Ni and Ni(80)Fe(20) were deposited on 500 nm thick suspended Si-N thermal isolation platforms with integrated platinum strips designed originally to allow measurement of thermally generated spin currents (the spin Seebeck effect). The low thermal conductivity of the thin supporting Si-N structure results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
104
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 26 publications
5
104
0
Order By: Relevance
“…[22][23][24][25][26] The trouble with this configuration is that, in addition to generating an ANE voltage, the out-of-plane temperature gradient can also generate a spin current through the so-called longitudinal spin Seebeck effect (LSSE), 22,[27][28][29][30][31][32][33] which flows directly from the ferromagnetic (FM) into the adjacent non-magnetic metal (NM) and generates a voltage because of the inverse spin Hall effect (ISHE). In order to distinguish the spin Seebeck effect (SSE) and ANE, extensive efforts [34][35][36][37] have been made to compare the voltage in different temperature gradient configurations. However, it is quite challenging to define precisely the out-of-plane temperature gradient which is established over a few nm thickness.…”
mentioning
confidence: 99%
“…[22][23][24][25][26] The trouble with this configuration is that, in addition to generating an ANE voltage, the out-of-plane temperature gradient can also generate a spin current through the so-called longitudinal spin Seebeck effect (LSSE), 22,[27][28][29][30][31][32][33] which flows directly from the ferromagnetic (FM) into the adjacent non-magnetic metal (NM) and generates a voltage because of the inverse spin Hall effect (ISHE). In order to distinguish the spin Seebeck effect (SSE) and ANE, extensive efforts [34][35][36][37] have been made to compare the voltage in different temperature gradient configurations. However, it is quite challenging to define precisely the out-of-plane temperature gradient which is established over a few nm thickness.…”
mentioning
confidence: 99%
“…In a thermal gradient, the temperature difference ∆T between two contacts gives rise to a thermopower V T = −S∆T with S being the material's Seebeck coefficient. Spin-dependent Seebeck coefficients have been observed in various nanomagnetic systems like thin films 10,11 , multilayers 12 , tunnel junctions [13][14][15] , and nanowires 16,17 . In the latter, magnetization reversal often occurs by the nucleation and propagation of a single magnetic domain wall (DW) enabling promising applications [18][19][20] .…”
mentioning
confidence: 99%
“…Here, the precise control of the temperature gradient is essential to identify and avoid spurious thermoelectric effects, in particular, in the transverse SSE configuration. [6][7][8][9] Using laser-heating of a yttrium-iron garnet/platinum hybrid structure in the longitudinal SSE configuration, Weiler et al reported spatially resolved measurements of both the anomalous Nernst effect (ANE) and the SSE. 10 In lateral FM/normal metal (NM) structures similar to the transverse SSE geometry, the effect of local temperature gradients have only been studied using Joule heating.…”
mentioning
confidence: 99%